2011
DOI: 10.3390/ma4081345
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Tension Test of Slender Reinforced Early Age Concrete Members

Abstract: The present study aims to obtain the tensile properties of early age concrete based on a uniaxial tension test employing RC slender members. First, the paper shows that concrete strain is equal to the strain of rebar at the mid-span of the RC member. The tensile Young’s modulus and the strain capacity of early age concrete are estimated using strain measurements. The experiment indicated that the tensile Young’s modulus at an early age is higher than the compressive modulus. This observation was similar to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Mimura et al [5] reported that the tensile Young's modulus based on the direct tension test by using the slender reinforced concrete (RC) specimen is higher than the compressive modulus (secant modulus) at early age. Swaddiwudhipong et al [6] also investigated tensile behavior of concrete at early age by using the direct tension test.…”
Section: Introductionmentioning
confidence: 99%
“…Mimura et al [5] reported that the tensile Young's modulus based on the direct tension test by using the slender reinforced concrete (RC) specimen is higher than the compressive modulus (secant modulus) at early age. Swaddiwudhipong et al [6] also investigated tensile behavior of concrete at early age by using the direct tension test.…”
Section: Introductionmentioning
confidence: 99%
“…Young's modulus in Japan is generally a secant modulus obtained from a compression test. Mimura et al [5] reported that the tensile Young's modulus based on the direct tension test by using the slender reinforced concrete (RC) specimen is higher than the compressive modulus (secant modulus) at early age. Swaddiwudhipong et al [6] also investigated tensile behavior of concrete at early age by using the direct tension test.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in the life-cycle analysis of concrete structures, especially for cracking analysis and construction management of RC structures during the construction period [6][7][8][9][10]. Most of these studies, however, focused on the development of http bond strength s 1 .…”
Section: Introductionmentioning
confidence: 99%